TOLERANCE AS AN INTEGRAL PRINCIPLE OF MULTICULTURALISM IN UZBEKISTAN - Муртазаева Р. Х. (TARIXIY TADQIQOTLAR, 2025)
This article examines the concept of multiculturalism, widely prevalent in the modern world, as a response to objective processes occurring in contemporary conditions. The reasons for the emergence of this policy are outlined, a brief summary of the essence of multiculturalism is provided, and various approaches to this issue are presented. Variants of multicultural policy and emphasizes the particularities of implementing this policy in Uzbekistan will be discussed in the article. Special attention is given to the management of a multinational and multicultural society in the Republic of Uzbekistan, at the core of which lies tolerance.